Pengaruh Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), dan Financing Deposite Ratio (FDR) Terhadap Return On Aset (ROA) Pada Bank Umum Syariah dan Unit Usaha Syariah di Indonesia Tahun 2018-2020 - Siti Aisyah Siregar (Fisarrearch, 2021)
Based on the type of problem studied, the research approach used is associative. The data collection technique used is a documentation study by collecting data from the monthly financial reports of Islamic Commercial Banks and Sharia Business Units in Indonesia for 2018-2020 contained in the Islamic banking statistical reports. The data analysis technique used in this research is multiple linear regression. The results showed that partially the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Financing Deposite Ratio (FDR) variables had no and no significant effect on Return On Assets (ROA). Meanwhile, simultaneously the variables of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Financing Deposite Ratio (FDR) have a significant influence on Return On Assets (ROA) in Islamic Commercial Banks and Sharia Business Units in Indonesia in 2018-2020.